A feasibility study on CO2 sequestration using the neutralization process of acid mine drainage. Issue 6 (1st November 2016) - Lee, Hyun-Cheol; Min, Kyoung-Won; Seo, Eui-Young
Abstract: Among various technologies for capturing and storing CO2, mineral carbonation technology stores CO2 by reacting natural minerals and industrial by-products containing a lot of Ca or Mg with CO2, and resultantly forming carbonate minerals. Mineral carbonation is one of the safest methods for the sequestration of CO2 as thermodynamically stable carbonate minerals. As a method for CO2 sequestration, this study utilized the neutralization process of mine drainage using hydrated lime. This method captures CO2 through CO2 injection into the neutralization process, resultantly forming calcium carbonate. The carbonation treatment was conducted using mine drainage collected from abandoned coal mines. The carbonation treatment of the neutralized mine drainage samples from three mine areas resulted in forming calcite precipitates of different amounts, and no additional environmental problems occurred through CO2 injection into the mine drainage. The estimated capacity of CO2 sequestration through the carbonation treatment of mine drainage from one mine area was of a considerable level (0.54 g CO2 /kg mine drainage). Additionally, for CO2 immobilization efficiency, it is necessary to estimate the optimum volume of CO2 injection through thorough preliminary tests. Conclusively, CO2 sequestration using the neutralization process of mine drainage can be evaluated as a positive technique in terms of sustainable development.